Merry work: libraries and citizen science. (12th September 2018) - Ignat, Tiberius; Ayris, Paul; Labastida I Juan, Ignasi; Reilly, Susan; Dorch, Bertil; Kaarsted, Thomas; Overgaard, Anne Kathrine
This article highlights important new opportunities for libraries by analysing the roles they could potentially play in citizen science projects. Citizen science is one of the eight pillars of open science identified by the Open Science Policy Platform, an EC Working Group. The authors of the article suggest that roles for libraries wishing to support or engage in citizen science could include contributing to specific skills development; building and maintaining collections of protocols, data forms and educational materials; contributing to making data FAIR; supporting new communication roles; participating in recruitment and helping volunteers to participate in projects; participating in marketing activities; building further advocacy and developing or implementing a toolkit for citizen science projects. Several of these roles are illustrated by contributing authors in case studies from their institutions, where citizen science has already been embraced: University College London, the University of Barcelona, the University of Southern Denmark and Qatar National Library. This article thus presents a snapshot of what libraries have so far achieved in this sphere and the challenges and opportunities which remain.